2021
DOI: 10.1016/j.ejon.2021.101923
|View full text |Cite
|
Sign up to set email alerts
|

A moment just for me – parents’ experiences of an intervention for person-centred information in paediatric oncology

Abstract: Information can help parents of children with cancer by reducing uncertainty and giving them a sense of control in a chaotic situation. Although providing information to parents is a core activity of paediatric oncology nursing, few studies focus on interventions for informing parents. Thus, the aim of this study is to evaluate parents' experiences after participating in a person-centred information intervention for parents of children with cancer. Method: This study is part of a process evaluation of a person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Participants in the intervention did, however, demonstrate higher levels of knowledge in certain domains (biophysiological and functional) than the control group. This is also mirrored in the separate qualitative evaluation of this study, where parents in the intervention arm reported a deeper understanding of their entire situation (Ringnér et al, 2021).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Participants in the intervention did, however, demonstrate higher levels of knowledge in certain domains (biophysiological and functional) than the control group. This is also mirrored in the separate qualitative evaluation of this study, where parents in the intervention arm reported a deeper understanding of their entire situation (Ringnér et al, 2021).…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, the topics raised in the intervention varied from consequences of the disease and treatment on the child's health to emotional aspects of the parents’ situation. Encouraging parents to choose topics according to their own specific wishes and needs and arranging for them to discuss these with a competent and compassionate IN (Ringnér et al, 2021) reflect core components of person-centered care that aims to offer a respectful and individualized holistic nursing approach based on the person's choice (Morgan & Yoder, 2012). This is further in correspondence with recommendations about giving parents an opportunity to “dig deeper” into specific topics later in the treatment trajectory (Landier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One study was conducted in both USA and Saudi Arabia (49). Ten studies used non-randomized controlled trial intervention (36-39, 42, 43, 45-48), four studies were randomized controlled interventional studies (34,35,44,49), and two study used qualitative interviews (40,41). All studies selected for nal analysis were published from 2014 to 2022.…”
Section: 1 Study Characteristicsmentioning
confidence: 99%
“…All studies selected for nal analysis were published from 2014 to 2022. Four studies were published in 2019 (35,36,44,48), another four studies in 2021 (38,41,43,49), two studies in 2022 (34,40), two studies in 2018 (39,47) and one study in 2014 (37) and 2015 (42).…”
Section: 1 Study Characteristicsmentioning
confidence: 99%
“…In a qualitative study sharing the experiences of families regarding end‐of‐life communication in pediatric oncology, families expressed the need for continuous, open, and supportive communication during the disease process, as well as in the end‐of‐life phase (Robert et al, 2022). Studies investigating the impacts of effective communication processes with children with cancer and their families have found that it facilitates the family's decision‐making process, reduces uncertainty regarding the situation by fostering a sense of control, enables families to more easily express their emotions, supports hope throughout the process, and enhances the quality of life for both the children and their families (Kerr et al, 2019; Ringnér et al, 2021; Sisk, Harvey, et al, 2022; Sisk, Keenan, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%